Epidemiological & Clinical Profile of Patients Presented with Mandible Fracture in a Tertiary Care Hospital (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Mandible is the second most commonly fractured bone after nasal bone, though it is the largest and strongest facial bone. Fractures of the mandible can involve only one site or can often involve multiple anatomic sites. It account for 36% to 59% of all maxillofacial fracture. The large variability in reported prevalence is due to a variety of contributing factors such as gender, age, environment, and socio-economic status of patient, as well as the mechanism of the injury. The most favorable site of fracture (in descending order) in mandible is the body, angle, condylar region, symphysis, and coronoid process. The descriptive type of cross sectional retrospective study was undertaken to determine the epidemiological & clinical profile of patients presented with fractures of mandible and their different methods of treatment modalities. Four hundred and thirty five patients with mandible fractures were treated during the year 2014-2015. A review of patient’s record was conducted. Data regarding age, gender, cause of fracture, anatomic site and treatment modalities were reviewed. There was higher prevalence in male (3.9:1), with occurrence peak between 21-30 years. The principal causes of fracture in this study were RTA (Road Traffic Accidents) representing 54.02% followed by physical assault 17.24%, Fall, Sports injury, Blow by heavy objects, Tube well injury & others which includes Tire blast injury, Gunshot injury, Iatrogenic cause, Pathological fracture, Boat handle injury, Penetrating injury by metal etc. The most injured sites were in parasymphysis (26.31%) followed by angle of mandible 17.89% then symphysis, condyle, body of mandible, dentoalveolar, ramus, coronoid process of mandible. Most patients (70.11%) of mandible fractures were treated by closed reduction (arch bar, arch bars with intermaxillary fixation IMF, eyelet wiring & lateral compression plate) & 21.83% of patients were treated with open reduction (miniplates fixation. 3D plate fixation) .Only 8.05% patients were managed by conservative approach. This study reflects patterns of mandible fracture within the community and discuss various methods of mandible fracture management in the department of Maxillofacial casualty in Dhaka Dental college hospital. It is hoped that information presented here will be useful to the government agencies and health care professionals involved in planning future programs of prevention & treatment of mandible fracture.J Bangladesh Coll Phys Surg 2018; 36(3): 107-111